Varicella‐zoster virus in actively spreading segmental vitiligo skin: Pathological, immunochemical, and ultrastructural findings (a first and preliminary study). (9th October 2022) - Gauthier, Yvon; Lepreux, Sebastien; Cario‐Andre, Muriel; Rambert, Jérome; Dakdaki, Adrien; Lafon, Marie‐Edith; Abouqal, Redouane; Benzekri, Laila
Abstract: Segmental vitiligo (SV) is a unilateral subtype of vitiligo which is clinically characterized by a cutaneous depigmentation and histologically by a melanocyte loss from the epidermis and hair follicle reservoirs. To date, its pathogenesis remains a mystery. In many cases, this skin depigmentation shares several clinical features and dysfunctions with herpes zoster (HZ). So, for the first time, we examined whether any nucleus and cell fusion associated with a positive immunolabelling of varicella‐zoster virus (VZV) and VZV mature virions could be found in SV skin samples as in herpes zoster (HZ). A total of 40 SV samples were used for histological and immunochemical studies. Control samples were obtained from three HZ, and 10 generalized vitiligo lesions. For ultrastructural study, three recent SV and one HZ as controls were recruited. Here, we report that nuclear fusion in epidermal cells were statistically associated with recent SV ( p  < .001), whereas syncytia formation was associated with long‐lasting SV ( p  = .001). A positive detection of VZV antigen was statistically associated in the epidermis with recent SV and in the dermis with long‐lasting SV ( p  = .001). Finally, the discovery of mature virions in 3/3 recent SV samples provides additional arguments for our viral hypothesis.